2004
DOI: 10.1136/emj.2003.005413
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled comparison of continuous positive airways pressure, bilevel non-invasive ventilation, and standard treatment in emergency department patients with acute cardiogenic pulmonary oedema

Abstract: Background: Continuous positive airways pressure (CPAP) and bilevel non-invasive ventilation may have beneficial effects in the treatment of patients with acute cardiogenic pulmonary oedema. The efficacy of both treatments was assessed in the UK emergency department setting, in a randomised comparison with standard oxygen therapy. Methods: Sixty patients presenting with acidotic (pH,7.35) acute, cardiogenic pulmonary oedema, were randomly assigned conventional oxygen therapy, CPAP (10 cm H 2 O), or bilevel ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 22 publications
4
85
0
5
Order By: Relevance
“…This result compares favourably with the study by Kosowsky et al, reporting an in hospital intubation rate of 7 out of 19 (37%). Intubation rate and overall mortality of the present study is in line with recent reports on the in-hospital [4,[7][8][9][10]27] and out-hospital [12] application of CPAP and Pressure Support Ventilation in ACPE. Oxygen saturation improved, respiratory rate, heart rate, and blood pressure decreased in both groups.…”
Section: Efficacy Of Helmet Cpapsupporting
confidence: 80%
See 3 more Smart Citations
“…This result compares favourably with the study by Kosowsky et al, reporting an in hospital intubation rate of 7 out of 19 (37%). Intubation rate and overall mortality of the present study is in line with recent reports on the in-hospital [4,[7][8][9][10]27] and out-hospital [12] application of CPAP and Pressure Support Ventilation in ACPE. Oxygen saturation improved, respiratory rate, heart rate, and blood pressure decreased in both groups.…”
Section: Efficacy Of Helmet Cpapsupporting
confidence: 80%
“…[2][3][4][5][6][7][8][9][10]. Despite this background, reports of CPAP application in prehospital setting are, to our knowledge quite limited.…”
Section: Out Of Hospital Use Of Cpapmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies revealed that, CPAP improved arterial oxygenation (PaO 2 ), and reduces endotracheal intubation rate [9][10][11] and mortality rate in ACPE [12,13]. However, other studies failed to show these effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%